Function spaces and pseudo-differential operators on vector bundles - Uusluoto, Veli-Pekka (2019)
The objective of this Master thesis is to give coordinate-free deﬁnitions of certain concepts in modern analysis on vector bundles and to apply these tools to elliptic partial diﬀerential equations. Topics that we cover are distribution theory, Sobolev spaces and pseudo-diﬀerential operators.